Patients’ satisfaction of surgery for resistant cases of de Quervain’s disease - Das, KP; Talukdar, DC; Chowdhury, RM; Islam, A; Datta, NK; Shoma, FK; Islam, MN (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10541 J. Dhaka Med. Coll. 2011; 20(2): 146-152